2014
DOI: 10.1186/preaccept-1226509013142020
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study on the temporal and micro-spatial distribution of Galba truncatula in four farms in Belgium as a base for small-scale risk mapping of Fasciola hepatica

Abstract: Background: The trematode parasite Fasciola hepatica causes important economic losses in ruminants worldwide. Current spatial distribution models do not provide sufficient detail to support farm-specific control strategies. A technology to reliably assess the spatial distribution of intermediate host snail habitats on farms would be a major step forward to this respect. The aim of this study was to conduct a longitudinal field survey in Flanders (Belgium) to (i) characterise suitable small water bodies (SWB) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Galba truncatula eDNA was also identified in four habitats where G. truncatula snails were not physically observed, indicating the assay has the potential to be more sensitive than the traditional method of detecting G. truncatula habitats by eye. Accurately identifying G. truncatula habitats using traditional methods may be difficult due to the variable nature of G. truncatula populations, which lead to short term variations in the snails’ visible presence and population size [ 10 , 11 ]. Specialist training is therefore required to identify potential habitats and to detect and differentiate between G. truncatula and other similar snail species commonly observed in overlapping niches [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galba truncatula eDNA was also identified in four habitats where G. truncatula snails were not physically observed, indicating the assay has the potential to be more sensitive than the traditional method of detecting G. truncatula habitats by eye. Accurately identifying G. truncatula habitats using traditional methods may be difficult due to the variable nature of G. truncatula populations, which lead to short term variations in the snails’ visible presence and population size [ 10 , 11 ]. Specialist training is therefore required to identify potential habitats and to detect and differentiate between G. truncatula and other similar snail species commonly observed in overlapping niches [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, as both F. hepatica and C. daubneyi are reliant on the same intermediate snail host, Galba truncatula [ 9 ], infection risk areas for these parasites will be limited to pastures harbouring these snails. Galba truncatula snails are highly dependent on wet climatic and environmental conditions [ 10 ], and their presence and densities will vary within fields and thus, specific fluke infection risk areas will be present on farms [ 11 ]. Identifying these risk areas will strengthen trematode infection risk models [ 12 ], and support farmers to implement farm management practices such as drainage, rotational grazing and fencing and thereby reduce contact between vulnerable animals and the infective metacercariae.…”
Section: Introductionmentioning
confidence: 99%
“…and highly acidic conditions, known to have a significant effect on DNA degradation (Strickler et al, 2015), were not observed at any study habitat. The negative association observed may therefore be a consequence of the relationship between G. truncatula snail presence and environment pH, although contradictory findings towards the snail's preference for either a slightly acidic or neutral pH are present in the literature (Urquhart et al, 1996;Charlier et al, 2014;Dreyfuss et al, 2018). However, as soil pH tends to be lower in areas exposed to heavy rainfall (Brady and Weil, 2002), it is feasible that habitats exhibiting a slightly acidic pH may be better suited to G. truncatula due to their humid conditions.…”
Section: Discussionmentioning
confidence: 94%
“…Unmanned aerial vehicles (drones), already used to capture habitats (e.g. small water bodies) of parasites and vectors at very small scales (Charlier et al ., 2014), have been recently used to facilitate the treatment of animals in remote grazing areas with the release of medicated baits (Yu et al ., 2017). The installation of micro-climate data loggers for the monitoring of soil surface temperature and humidity in grazing areas, offers the possibility to identify the environmental conditions which favour the local abundance of intermediate hosts for snail-born parasitoses.…”
Section: Geographic Information Systems (Gis) – Bringing Complexity U...mentioning
confidence: 99%